Validity of a virtual reality endoscopic retrograde cholangiopancreatography simulator: can it distinguish experts from novices? - Georgiou, Konstantinos; Boyanov, Nikola; Antonakis, Pantelis; Thanasas, Dimitrios; Sandblom, Gabriel; Enochsson, Lars (Frontiers in Surgery, 2023)
There is a lack of evidence regarding the effectiveness of virtual simulators as a means to acquire hands-on exposure to Endoscopic Retrograde Cholangiopancreatography (ERCP). The aim of the present study was to assess the outcome and construct validity of virtual ERCP when training on the GI Mentor II simulator.A group of seven experienced endoscopists were compared with 31 novices. After a short introduction, they were requested to carry out three virtual ERCP procedures: diagnosing and removing a common bile duct stone, diagnosing, and taking brush cytology from a hilar stenosis and, finally, diagnosing and treating a cystic leakage with a bile duct stent. For each task, total time required to complete the task, time required to correctly view the papilla, total time of irradiation, time to deep cannulation, time to define diagnosis, time to completed sphincterotomy, and time to complete the respective intervention was measured for each task.Cannulation of the bile duct, correct diagnosis, sphincterotomy and time to complete intervention was assessed by an assessor blinded to the status of the endoscopist that performed the virtual ERCP.Time required to visualize the papilla and to cannulate deeply when removing bile duct stone was significantly shorter for the experts (both p<0.05). Time to visualize the papilla, cannulate deeply, reach diagnosis, complete sphincterotomy and complete intervention was significantly shorter for the experts when managing cystic leakage (all p<0.05). In diagnosing and taking brush cytology from a hilar stenosis there was only a trend towards that the experts needed less time for the deep cannulation of the bile duct (p=0.077).The performance differed between experts and novices, especially in the management of cystic leakage. This corroborates the construct validity of the GI II Mentor simulator.